IDENTIFICATION OF SLOPE FAILURE USING 2-D RESISTIVITY METHOD - Mohd Muztaza, Nordiana; Ghafar, Syafiqah Hanis Mohd Abd; Sukri, Muhamad Syahir; Jinmin, Jinmin (2018)
A study has been conducted to analyze the slope failures features and the factors that contribute to the landslide occurrence at Restu, Saujana and Tekun (RST) Complex, USM by using the 2-D resistivity method. Five survey lines were conducted with 100 m length and 2.5 m minimum electrode spacing. The data obtained were transferred into the computer for further processing and was presented in 2-D resistivity inversion model via Res2Dinv and Surfer vl1.0 software. The inversion models convey the subsurface structure on each line in which was represented by the resistivity values. The range of resistivity values were determined and classified into three classes for interpretation. The saturated zones, weathered granite and fresh granite were classified with range values of 1-400 Qm, 1500-5000 Qm and greater than 5000 Qm respectively. The saturated zones may compose of alluvium in which commonly consist of clay, silt and sand. Other features such as presence of boulders was indicated by isolated high resistivity values, boulders overlie saturated zone and presence of fracture were also determined as indicated by the resistivity variations of the inversion models. These features can be the influence to trigger the landslide event in the early stages. Apart from precipitation as a major factor of the phenomenon, slope angle can also be one of the important factors to be aware to determine slope stability. Precipitation can affect the soil strength and texture while the slope angle can determine slope's class oflandslide risk. This study area has been classified ofhaving higher risk oflandslide event.